(untitled) (Social and Environmental Law Journal, 2024)
The aim of this paper is to make visible and to leave in point for reflection on the dynamizing role that has the component of pedagogical and investigative practice in the processes of guarantee of rights, as well as the enjoyment of the same ones, not only in academic and university scenarios, but also in the exercise of life and in the generation of contributions to the development of the territories where the students of the School of Education Sciences of the UNAD dynamize their life experiences.